The Effectiveness of Suggestopedia in Developing Basic English Skills among Primary School Students in Libya: A Case Study in the Assaba Area (Al-Qods Primary School) - Abdulmjeed Almogatef; Waleed Aldhawi Almishraqi (Journal of Scientific and Human Dimensions, 2026)
This research looked into how well Suggestopedia helps seventh graders build basic English skills at Al-Qods Primary in Assaba, Libya. The setup wasn't fully random - two groups took part: one learned with Suggestopedia, while the other followed regular teaching ways. There were thirty pupils involved; they did tests before and after focusing on reading, writing, listening, plus talking abilities. Besides that, short surveys captured what learners thought about their own drive, self-assurance, along with interest during lessons.ANCOVA findings revealed the experimental group did notably better on post-tests than the control group once pre-test levels were accounted for (F = 13.8, p = .002). On top of that, students learning via Suggestopedia mentioned feeling more motivated, joining in more actively, worrying less, also gaining stronger confidence when speaking English.These results show adding Suggestopedia methods - like calm activities, tunes, mental images, or upbeat hints - might really help kids learn English better in early schools across Libya. Instead of old routines, educators and program designers could use these ideas to build lessons that support each student’s mindset while keeping them involved.
Keywords: Suggestopedia; Language Learning; Reading Skills; Writing Skills; Listening Skills; Speaking Skills; Primary School Students; Libya; Motivation; Engagement; Confidence